Amazing animal journeys - Marsh, Laura F. (New York : National Geographic Society, 2010)
Every year like clockwork, animals both big and small are driven by a natural instinct to move, in order to survive. On both land and sea, they fight the odds and the forces of nature to breed, feed, or lead and carry on for future generations. This reader is an introduction to the treacherous trek of the zebra, walrus, and Christmas Island red crab to overcome obstacles that include hungry cheetahs, stinging yellow crazy ants, and even their fellow species to make the often impossible journey of their lives.
"National Geographic kids"-Cover.
Includes index.
b
b
Keywords: Animal migration -- Juvenile literature